Who Will Govern the New World?the Present and Future of the G20. - Renmin University of China, Chongyang Institute for Financial Studies (Stuttgart : Ibidem Press, 2016)
How can the G20 fulfill their role most efficiently in the post-crisis era, and what role do the emerging economies play in the new global economic order? This timely volume provides an overview of the most important challenges ahead for the G20, especially China.
G20â#x80;#x99;s Future and Chinaâ#x80;#x99;s Role in the G20G20 Governance for the Future: Performance, Prospects, Possibilities and Chinaâ#x80;#x99;s Role; Part 4 G20 Think Tanks: Joint Statement; â#x80;#x9C;Great Finance, Great Cooperation, GreatGovernanceâ#x80;#x9D; International Think Tank Conference: Joint Statement; Afterword:Think Tanks, Public Diplomacy and the Chinese Dream.
Print version record.
eBooks on EBSCOhost
Keywords: Group of Twenty; Group of Twenty; International economic relations; Economic development -- 21st century; China -- Economic policy -- 2000-; Développement économique -- 21e siècle.; Chine -- Politique économique -- 2000-; BUSINESS & ECONOMICS -- Economics -- General; BUSINESS & ECONOMICS -- Reference; Economic development; Economic policy; International economic relations; China; Since 2000; Electronic book